Pendidikan Jasmani Perspektif Sayyid Qutub - DZAKY MUBAROK (Jurnal Pendidikan Educandum, 2022)
The purpose of this study was to determine how the physical education based perspective Sayyid Qutub and how big is the application of physical education is based on the perspective of Sayyid Qutub in Indonesia today. The method used to analyze is a method of hermeneutics, namely by capturing the essential meaning depending on the context at the time of data collection, then menginterpretsi the data to be understood in context of this present time, which is reviewing physical education in perspective Sayyid Qutub. The results showed 1) that political reform and social justice is not in the hands of the communists, but tucked away in the verses of the Qur’an and thenature of islam it self. 2) The importance of physical education is confirmed also by Sayyid Qutub, who interpreted tarbiyah is the maintenance of physical learners and helped foster an aura of maturity mental attitude of moral al-karimahon self learners. 3) Thought and Sayyid Qutub perspectives in the field of education, especially physical education irrelevant to be applied in Indonesia.